Unfunded Mandates and the Economic Impact of Decentralisation. When Finance Does Not Follow Function - Rodríguez-Pose, Andrés; Vidal-Bover, Miquel (Political studies, 2024)
Decentralisation has frequently been sold as a means to increase well-being and development. Yet, questions remain as to whether decentralisation improves economic performance. This is possibly because decentralisation processes have often led to ‘unfunded mandates’, that is, a mismatch between the powers transferred to subnational tiers of government and the resources allocated to them. In this article, we analyse how unfunded mandates shape regional economic growth across 518 regions in 30 Organisation for Economic Co-operation and Development countries over the period 1997–2018. There is a negative, statistically significant, and robust impact of unfunded mandates on economic growth. This effect is higher in more politically and less fiscally decentralised regions and in regions with a higher level of wealth. Unfunded mandates thus represent a serious drag on the potential positive economic effect of political decentralisation. Hence, for those benefits to materialise, better not more decentralisation – ensuring that finance follows function – should be pursued.